Ответы и объяснения

Лучший Ответ!
2011-12-16T23:46:35+04:00

log₁,₃(16-5x)^½ = log₁,₃(2x-5)                      16-5x>0                  2x-5>0

(16-5x)^½ = (2x-5)                                       5x<16                     2x>5

 16-5x = (2x-5)²                                             x<3,2                      x>2,5

4x²-20x+25=16-5x                                        2,5<x<3,2

4x²-20x+25-16+5x=0

 4x²-15x+9=0

D= 15²-4*4*9= 225-144=81

 

x₁=(15-9)/2*4 = 6/8 = 3/4

x₂=(15+9)/2*4 = 24/8 = 3

 

otvet: 3